Praktik Pandangan Tokoh Masyarakat dan Tokoh Adat terhadap Praktik Sedekah dari Sumber Rezeki yang Tidak Biasa di Desa Mojopuro - Riska Dewi Andriyani; Kholifah Kholifah; Ridho Maulana Apriandi; Tasman Tasman (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines the views of community and traditional leaders on the practice of giving alms derived from unusual sources of income in Mojopuro Village. The tradition of giving alms in Mojopuro has strong cultural roots and social values, reflecting a blend of Islamic teachings and local wisdom. However, historically, almsgiving has sometimes come from less than halal sources, such as gambling proceeds, which were once considered commonplace due to limited religious understanding. This study employed a descriptive qualitative method, using interviews with community and traditional leaders as key informants. The results show a significant shift in how the community interprets almsgiving. Religious leaders now emphasize the importance of halal sources of income and sincere intentions in giving, while traditional leaders emphasize social values such as mutual cooperation and caring for others. This transformation reflects a shift from traditional practices to a deeper religious understanding, without diminishing the values of togetherness that are characteristic of Mojopuro. Thus, the tradition of giving alms in Mojopuro is not only a form of worship but also a means of fostering morality and social solidarity that persists amidst changing times